PENGARUH LOOSE PART TERHADAP KEMAMPUAN MOTORIK HALUS ANAK USIA 5-6 TAHUN DI TK NEGERI PEMBINA BARAT KOTA PAYAKUMBUH - Aulia Afrilita; Rakimahwati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research is to analyze the effectiveness of Loose Part on children's fine motor skills at the Pembina Barat State Kindergarten, Payakumbuh City. This research uses quantitative methodology based on an experimental strategy. The samples in this study were class B1 and Class B3, each consisting of 12 children. The sampling technique in research is cluster sampling. Data collection techniques include verbal tests and action tests. Data analysis techniques use normality tests, homogeneity tests, hypothesis tests and data collection tools use statement sheets. Then it is processed using a difference test (t-test) with the help of the SPSS 26 for Windows application. The results show that in the control class the average score for the pre-test was 11.66 and the post-test was 15.5, so the difference between the controls was 3.83. Apart from that, there was also an increase in the experimental class with an average score for the pre-test of 11.83 and post-test of 16.83, so that the difference in the experimental class was 5. In both classes, the research results were equally visible, but the experimental class had a higher average score than the control class. Thus, it can be concluded that there is an influence of loose parts on the fine motor skills of children aged 5-6 years at the Pembina Barat State Kindergarten, Payakumbuh City.